What if I Get Busted? Deception, Choice, and Decision-Making in Social Interaction - Sip, Kamila E.; Skewes, Joshua C.; Marchant Agustus, Jennifer L.; McGregor, William B.; Roepstorff, Andreas; Frith, Christopher D. (Frontiers in Neuroscience, 2012)
Deception is an essentially social act, yet little is known about how social consequences affect the decision to deceive. In this study, participants played a computerized game of deception without constraints on whether or when to attempt to deceive their opponent. Participants were questioned by an opponent outside the scanner about their knowledge of the content of a display. Importantly, questions were posed so that, in some conditions, it was possible to be deceptive, while in other conditions it was not. To simulate a realistic interaction, participants could be confronted about their claims by the opponent. This design, therefore, creates a context in which a deceptive participant runs the risk of being punished if their deception is detected. Our results show that participants were slower to give honest than to give deceptive responses when they knew more about the display and could use this knowledge for their own benefit. The condition in which confrontation was not possible was associated with increased activity in subgenual anterior cingulate cortex (subACC). The processing of a question which allows a deceptive response was associated with activation in right caudate and inferior frontal gyrus (IFG). Our findings suggest the decision to deceive is affected by the potential risk of social confrontation rather than the claim itself.